Intracytoplasmic Sperm Injection Cycle Outcomes in Women Aged 40 Years and Over - Aldemir, Oya; Ozelci, Runa; Dilbaz, Serdar; Dilbaz, Berna; Baser, Emre; Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: The main detrimental factor in female fertility is maternal age. Clinical pregnancy and live birth rates decline gradually with age and this decline is dramatical over 40 years. In this study, we examined the in vitro fertilization/intracytoplasmic sperm injection cycle outcomes of women aged 40 years and over. Study Design: This retrospective cohort study included 336 fresh in vitro fertilization/ICSI cycles of women aged ≥40 years. Six groups, stratified by one-year intervals were composed according to age: 40 years; 41 years; 42 years; 43 years; 44 years, and ≥45 years. The primary outcomes were the clinical pregnancy and live birth rates. Results: The clinical pregnancy rate was 18.6% in 40 years old women and it decreased to 4% in women aged ≥45 years. The live birth rates in women aged 40 and 41 years (10% and 6.1% respectively) were higher than the live birth rates in women aged 42 and 43 years (4.3% and 3.8% respectively). There was no live birth in women aged 44 and over. The miscarriage rate was 46.2% at age 40 and it increased to 100% at age 44 and over. Conclusion: The clinical pregnancy and the live birth rates decreased significantly with every single year after 40 years of age. In patients between the ages of 40-43, the live birth rate is acceptable but starting an in vitro fertilization cycle beyond 43 years of age does not seem to be reasonable.